APPRAISAL OF PARENTS ON PRE-MARITAL HIV SCREENING IN A RURAL, NORTHEAST COMMUNITY, NIGERIA - YAHYA SJ; WUDIRI ZW; OMOTARA BA; MSHELIA H (Ntec Specialist, 2014)
Background: Sub-Saharan Africa has two-thirds of global HIV/AIDS burden. Nigeria has a prevalence of 4.1%, with transmission mainly through heterosexual intercourse. Sixty percent of new infections with HIV occur within the age group 15-29 years and most marriages especially with respect to females are conducted within this age group. Marriages are usually contracted by parents, therefore their knowledge and attitude to HIV status is deemed important. Objective: To assess the knowledge and attitude of parents towards premarital HIV Screening. Method: A cross-sectional descriptive study was conducted among 400 randomly selected parents in three districts of Bama Local Government Area (LGA) using a 36 item structured questionnaire administered to respondents in their homes. Results: A total of 397 respondents (99.3%) have heard of HIV/AIDS, radio (67.3%) being the major source. Sexual intercourse (97.3%), the use of contaminated instruments (42.5%), transmission of infected blood and blood products (17.8%) were identified as modes of transmission. However, only 8.5% identified mother to child transmission. Majority (98.8%) were aware that the disease is preventable mostly through faithfulness to partner (68.8%), premarital abstinence (64.8%) and Condom use (17.5%) while avoidance of contaminated instrument (9%) were also identified as modes of prevention. Majority (96.8%) of parents were aware of premarital HIV Screening. Majority of the parents (97.7%) approve of premarital HIV screening. Many (87.8%) of parents were not aware of the availability of HIV testing facility. Conclusion: The awareness and knowledge of HIV/AIDS in Bama LGA is high among parents. There was also a high level of awareness of PMHS with a positive attitude of parents toward it